Military aviation disasters : significant losses since 1908 - Gero, David (Sparkford, Nr Yeovil, Somerset, UK : Patrick Stephens Limited ; Newbury Park, Calif. : Haynes North America, 1999)
Every year, a number of military aircraft ranging from single-seat fighters to fully laden cargo planes are lost in accidents. Because these disasters often occur in remote corners of the world and rarely involve members of the general public, they seldom attract the sort of media attention given to those disasters which involve civil aircraft.
In this, the first volume to systematically document and describe military aviation disasters, author David Gero has assembled a century of mishaps, beginning with the loss of a Wright flyer that was being demonstrated for the U.S. Army in 1908. In addition to the aircraft types and serial numbers, and times, places, and causes, there are copies of accident reports and previously unpublished photographs of crash sites. Also includes combat losses involving transport aircraft and gliders.
"RB574"--Spine.
Includes bibliographical references (pages 7-8) and index.
Keywords: Airplanes, Military -- Accidents -- History; Aircraft accidents -- History; Aircraft accidents; Airplanes, Military -- Accidents; History